Student food security: the (dis)connection between student food experiences, sustainability and green spaces from the lens of food security - Drewett, Jessica (Department of Environmental and Geographical Science, 2019)
The food security of university students in South Africa is an area of research which is becoming increasingly researched and recognised. Internationally, there has been research into university student food security, recognition of student food insecurity and the links to academic success, and the idea of secure campus food systems. Approaches documented in the literature from the global North include the establishment of food banks and pantries, and the use of university green space in order to feed university students and decrease student food insecurity. Limited research on food security of university students in South Africa has been conducted, but this is increasing. Universities around the world are becoming increasingly aware and active in examining their ecological impacts as universities, and placing sustainability on the university agenda. This research explores the current narratives of student food security, campus food initiatives and the (dis)connection between green spaces and student food security responses at a university in South Africa. In order to achieve the research aim, three objectives were identified. The first objective was to review the global literature of university student food security, the use of green spaces on university campuses as a food security response. The second objective investigated student food security dialogues, and the third objective included the examination of university based food initiatives and university policy documents and reports, and assessing the integration of aspects of student food security. This exploratory research used a mixed methods approach, using a mixture of quantitative and qualitative data, by way of literature review, document analysis, online quantitative surveys and semi structured interviews in order to explore the narrative of student food security in South Africa, as well as the link between university campus sustainability and student food security. Dominant themes which arose from the research include food costs and affordability, in addition to food quality and health. It was found that there is a disconnection between student food experiences, sustainability and green spaces. While the links between green space and student food security may be relevant in Northern contexts, more pressing systemic issues require attention in the context of South Africa, thus adding to the complexity of how student food security is approached in the country. This exploratory research highlights the need for further research to be conducted in the area of student food security.